2023
DOI: 10.4236/ajibm.2023.134014
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Consumers Adoption of AI-Based Chatbots: The Role of Anthropomorphism

Abstract: Previous studies paid more attention to factors affecting consumers intentions and behaviors to adopt IT in the retail industry; however, little attention has been paid to factors affecting consumer intentions to adopt chatbots in the retails industry. This study utilizes technology acceptance models to explore these factors. Quantitative approach method using online survey was adopted to collect data from consumers in Saudi Arabia retail industry. We collected data from 903 consumers and analyzed it using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Focusing on the intention to use, using for information needs and reliable information were the strong reasons for the continued use of AI virtual assistants. Recent studies [50,[57][58][59] exploring other factors have identified factors such as anthropomorphism, trust, and assistants' personality traits to be influencing the acceptance of AI virtual assistants, indicating the emergence of various factors in continuing research. For instance, a trusting bond was developed within four days between a company chatbot and its users, which may take days with human therapists [57].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the intention to use, using for information needs and reliable information were the strong reasons for the continued use of AI virtual assistants. Recent studies [50,[57][58][59] exploring other factors have identified factors such as anthropomorphism, trust, and assistants' personality traits to be influencing the acceptance of AI virtual assistants, indicating the emergence of various factors in continuing research. For instance, a trusting bond was developed within four days between a company chatbot and its users, which may take days with human therapists [57].…”
Section: Discussionmentioning
confidence: 99%
“…These cues include the agent's name, communication style, pitch, and personality (refer to Figure 2). While previous studies have primarily focused on agents accessible via phones or generic devices (e.g., Moussawi et al (2020), chatbots in marketing including Alboqami (2023); Sheehan et al (2020), and other computer systems such as , AI-enabled mHealth apps present a considerably more intricate landscape. Unlike Siri, Alexa, Google Assistant, and Cortana, mHealth apps are tailored to address healthcare contexts, rendering them substantially more complex than the systems scrutinized in foundational studies (Liu & Tao, 2022).…”
Section: Introductionmentioning
confidence: 99%